Injury prevention in athletics: The race has started and we are on track - Edouard, P.; Alonso, J. M.; Jacobsson, J.; Depiesse, F.; Branco, P.; Timpka, T. (New Studies in Athletics, 2015)
The practice of athletics involves the risk of injury. Injury prevention and athlete health represent important issues for the athletes themselves plus all the stakeholders in the sport, including national athletics federations and international sports organisations. In this report, an international team of sport medicine experts describes the state of the art in this area and the efforts of the IAAF, European Athletics, the French athletics federation and the Swedish athletics federation to expand the knowledge. They find that the vast majority of studies to date are related to injury rates while necessary understanding of the mechanisms and risk factors of athletic injuries is still limited. Various prevention measures and/or strategies specific to certain injuries have been devised and proposed, however, unlike in football and some other sports, none of these have been scientifically validated for effectiveness. These clearly represent a second relevant direction to follow and develop. The authors conclude by recognising international and national athletics federations for their positive contributions in this area and calling on them to continue their support.